MENINGKATKAN KESADARAN MASYARAKAT DESA PRINGGAJURANG UTARA TERHADAP BENCANA LONGSOR MELALUI PENIDIKAN DAN PELATIHAN MITIGASI BENCANA - Salman; Aryaguna, Lalu Wangsa; Sumarti, Elinda; Anggraeni, Dea Tri Maya; Mintari Aprillisa; Isnani, Septiya Rahmatul; Nanda Salsabilah; Pratama, M.Febrian Ulmayadi; Wirantino, Lalu Pikya; Septiawan, Redza Dwi; Nasari, Linda (Universitas Mataram, 2024)
Disaster resilient villages (Destana) are villages/sub-districts that have the independent ability to adapt and face potential disaster threats, as well as recover immediately from the detrimental impacts of disasters. The aim of the Disaster Resilient Village is to realize development planning that contains efforts to prevent, prepare, reduce disaster risk and increase capacity for post-emergency recovery so that it can increase community awareness in North Pringgajurang village regarding landslides which often occur in several hamlet in the village. North Pringgajurang Village is one of the villages located in Montong Gading District, East Lombok, which consists of 8 hamlets. In order to realize the goal of a disaster resilient village in this village, the methods that will be implemented include carrying out socialization activities on landslide disaster mitigation and planting tree seedlings so as to create public awareness of the dangers of landslides and reduce the potential for landslides in North Pringgajurang village.